Uji Toksisitas Ekstrak Kloroform Cangkang dan Duri Landak Laut (Diadema setosum) Terhadap Mortalitas Nauplius Artemia sp - Aprilia, Hilda Ayu; Pringgenies, Delianis; Yudiati, Ervia (977-2407769)
Eggshells and spines of sea urchins (Diadema setosum) have toxins that can lead to certain biota surrounding death. Presumably the sea urchin has toxic compounds that can affect the surrounding environment. Because it needed a way to determine the toxic properties of sea urchin. Bioactive compounds contained in a previous study showing shells and spines of certain species of sea urchin pigment is coated by a black liquid that is stable. This fluid can be used as a mesh and skin coloring. It can also be used as fertilizer. This study aims to determine the lethal toxicity (LC50-24 h) of the chloroform extract of sea urchin of mortality Nauplius Artemia sp. The method used in this study is the experimental laboratory. Chloroform extract of the eggshells and sea urchin spines were tested using animal toxicity tests Nauplius Artemia sp.The results showed that the lethal toxicity (LC50-24 h) of the Nauplius Artemia sp in the chloroform extract of sea urchin eggshells at 133.58 ppm. As for the chloroform extract of sea urchin spines obtained results for 168.178 ppm. Chloroform extracts of both eggshells and sea urchin spines have potential activity as anti-microbial bio